Regulación española de la contratación colectiva y en origen de trabajadores extranjeros - Sánchez Trigueros, Carmen (Revista de Derecho, 2019)
The Law 4/2000 of 11 January on the rights and freedoms of foreigners in Spain and their social integration, has been, throughout its term, subject to various modifications, the last of which corresponds to the Law 2/2009 of 11 December, which amongother provisions has amended article 39 related to the quota of foreign workers; may be observed, as major innovations, the new name of the procedure as collective hiring at source and giving the Ministry of Labour and Immigration the authority for approval. The new wording of Article 39, introduced by the Law 2/2009 of December 11, empowers the Ministry of Labour and Immigration to approve an annual estimate of occupations and, where appropriate, the number of jobs that may be covered through the collective management of contracts at source in a given period that have access only those foreign workers who are not staying or residing in Spain. Moreover, the Ministry of Labour and Immigration, aware of the importance of hiring foreign workers as an instrument of management of migratory flows and the need to ensure coverage of jobs not covered by the national labor market, has considered convenient to approve the employment figures provided can be covered by the collective management of recruitment, previously proposed by the Autonomic Communities.